Enhancing Students' Learning Interest and Conceptual Understanding in Sociology: Using the Analogy Method and Canva Infographic Media - Iwan Ramadhan; Munawar Thoharudin; Hadi Wiyono; Sabirin Sabirin; Suriyanisa Suriyanisa (STAI Hubbulwathan Duri, 2024)
This study evaluates the effectiveness of combining the analogy method with Canva infographics to enhance conceptual understanding and student engagement in Sociology learning, a subject often perceived as abstract and unengaging. A quasi-experimental one-group pretest-posttest design was conducted with 36 grade XI Sociology 6 students at SMA Negeri 8 Pontianak. Data collection involved pretests, posttests, Likert-scale questionnaires, and observation sheets to assess understanding and engagement. The findings revealed a significant improvement in posttest scores (mean pretest = 62.5; posttest = 81.5; p 0.001). The gain index (G = 0.5278) indicated a moderate increase in conceptual understanding, while Cohen’s d value of 1.58 reflected a large effect size. The analogy method simplified abstract sociological concepts by linking them to students’ real-life experiences, while Canva infographics provided creative and systematic visualizations of complex ideas. This combination also encouraged critical and creative thinking, enhancing student engagement. The study highlights the potential of integrating analogy-based methods with digital tools like Canva to address challenges in teaching abstract subjects. The findings support constructivist and dual-coding theories, which emphasize experiential learning and the integration of verbal and visual information. This research demonstrates that analogy methods paired with Canva infographics significantly improve students’ understanding and engagement in Sociology. Further studies should explore the broader applicability of this method across diverse subjects, educational levels, and learning environments.